Mid-IR dual-wavelength difference frequency generation in uniform grating PPLN using index dispersion control - 常建华 孙青 葛益娴 王婷婷 陶在红 张闯 (Chinese physics B, 2013)
A novel widely tunable dual-wavelength mid-IR difference frequency generation （DFG） scheme with uniform grating periodically poled lithium niobate （PPLN） is presented in this paper. By using the temperature-dependent dispersion property of PPLN, the quasi-phase matching （QPM） peak for the pump may evolve into two separate ones and the wavelength spacing between them increases with the decrease of the crystal temperature. Such two pump QPM peaks may allow simultaneous dual-wavelength mid-IR laser radiations while properly setting the two fundamental pump wavelengths. With this scheme, mid-IR dual-wavelength laser radiations at around 3.228 and 3.548, 3.114 and 3.661, and 3.019 and 3.76 μm, are experimentally achieved for the crystal temperatures of 90, 65, and 30 ℃, respectively, based on the fiber laser fundamental lights.